Functional status and health-related quality of life of the Institutionalised elderly in selected Johannesburg areas - Uwumagbe, Iyare Brain (My University, 2017)
BACKGROUND: Global life expectancy is on the rise and it is contributing to the growth of the population proportion of the elderly. More and more elderly are getting institutionalised. Functional status decline has been found to influence institutionalisation in the elderly while health-related quality of life seems to be better among the community dwelling elderly compared to the institutionalised elderly. As a result, there is increased interest on the functional status and health-related quality of life (QoL) of the institutionalised elderly. OBJECTIVES: The objectives of the study were:  to determine the demographic profile of the institutionalised elderly in Alexandra, Orange Grove and Yeoville areas of Johannesburg.  to determine the health-related quality of life and functional status of the institutionalised elderly in Alexandra, Orange Grove and Yeoville areas of Johannesburg.  to determine the relationship between functional status and health-related QoL of the institutionalised elderly in selected Johannesburg areas.  to determine the predictors of functional status and health-related QoL of the institutionalised elderly in selected Johannesburg areas. METHOD: The study utilised a cross-sectional, quantitative descriptive design. Functional status was assessed using the Physical Self Maintenance Scale (PSMS) and the Instrumental Activities of Daily Living (IADL) scale while health-related QoL was assessed using the EQ-5D-5L. The functional status and health-related QoL of the participants were assessed as a onetime event over 11 weeks. The calculated sample size was 137 participants but only 116 residents met the inclusion criteria. Questionnaires were administered individually on participants who met the study inclusion criteria after obtaining consent to get activities of daily living (ADL), IADL and health-related QoL scores. Stata version 13 was used for data analysis. RESULTS: There were 105 participants, 66 (62.86%) female and 39 (37.14%) male. The mean age was 75.2 (±8.56) years and age range being 61-98 years. The median ADL score was 5. The median IADL score for female participants was 2 while the mean IADL score for male participants was 1.95±1.70. The median EQ-5D-5L index value was 0.69. Activities of daily living (r=0.685, p<0.001) and IADL (r=0.434, p<0.006 (male); r=0.369, p<0.003 (female)) were positively correlated with health-related QoL. The correlation between health-related QoL and ADL and that between QoL and IADL were strong and moderate respectively. Independent predictors of health-related QoL were race and religion. Religion was the only independent predictor of functional status (basic ADL) for both male and all participants. There was no independent predictor of functional status (IADL) for female participants. CONCLUSION: The age range of participants was a span of four decades of life beginning from the sixth decade. Females outnumbered male participants in the ratio 1.69:1. The functional status of participants was poor (IADL) to moderate (ADL). The health-related quality of life of participants was moderate. Functional status and health-related quality of life were positively associated with strong strength. Religion and race independently predicted functional status and health-related QoL. Although the data gotten from participants’ responses were sufficient for analyses, the findings from this study cannot be generalised to all the institutionalised elderly in the selected areas in Johannesburg because the number of residents who met the study inclusion criteria and participated in the study fell short of the calculated sample size. In essence, there is the need for more studies on the functional status and health-related quality of life of the institutionalised elderly.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg 2017
Keywords: Institutionalized Elderly; Quality of Life